Оцінка ефективності використання медіанного фільтру в цифровій обробці зображень - Лисенко, Б. С. (ХНУРЕ, 2023)
Evaluation of the effectiveness of the use of the median filter in digital image processing, as well as methods of improving the effectiveness of the median filter.
Keywords: медіанний фільтр; обробка зображень